Alpinia Oxyphylla Miquel Fruit Extract Activates MAPK-mediated Signaling of PAs and MMP2/9 to Induce Schwann Cell Migration and Nerve Regeneration. Issue 5 (May 2014) - Chang, Yung-Ming; Ye, Chi-Xin; Ho, Tsung-Jung; Tsai, Te-Neng; Chiu, Ping-Ling; Tsai, Chin-Chuan; Lin, Yueh-Min; Kuo, Chia-Hua; Tsai, Fuu-Jen; Tsai, Chang-Hai; Huang, Chih-Yang
Objectives: This study investigates the molecular mechanisms by which Alpiniae oxyphyllae fructus (AOF) promotes neuron regeneration. Methods: A piece of silicone rubber was guided across a 15 mm gap in the sciatic nerve of a rat. This nerve gap was then filled with different concentrations of AOF extract (0-200 mg/ml). We investigated the role of MAPK (ERK1/2, JNK and p38) pathways for AOF-induced matrix-degrading proteolytic enzyme (PAs and MMP2/9) production in RSC96 Schwann cells. Results: The results showed that AOF increased the expressions of uPA, tPA, MMP-9, and MAPKs in vivo. In vitro, our results show that treatment with AOF extract induces ERK1/2, JNK, and p38 phosphorylation to activate the downstream PAs and MMPs signaling expression. AOF-stimulated ERK1/2, JNK, and p38 phosphorylation attenuated by individual pretreatment with siRNAs or inhibitors (U0126, SP600125 and SB203580), resulting in migration and uPA-related signal pathway inhibition. Conclusions: Taken together our data suggests the MAPKs (ERK1/2, JNK and p38), PAs (uPA, tPA), MMP (MMP2, MMP9) regenerative and migration signaling pathway of Schwann cells regulated by AOF extract might play a major role in Schwann cell migration and damaged peripheral nerve regeneration.